A Rare Case of Neutrophil-Rich, ALK-Negative Anaplastic Large Cell Lymphoma in the Lung Mimicking a Pulmonary Abscess on 18F-FDG PET/CT. (March 2019) - Wang, Li-Juan; Wu, Hu-Bing; Zhang, Yin; Zhou, Wen-Lan; Wang, Quan-Shi
Abstract : Abstract: A 21-year-old man complained of cough, fever, and hemoptysis for 15 days. Peripheral neutrophil cell (33.8 × 10 9 /L) was markedly increased, and a mass in the left lung was detected by chest radiography. 18 F-FDG PET/CT was referred for characterizing the lesion and found a large mass with multiple cavities in the left lung, which had markedly high uptake of 18 F-FDG, mimicking pulmonary abscess. Surprisingly, the lesion was eventually proved to be neutrophil-rich anaplastic large cell lymphoma. After 4 cycles' chemotherapy, the lesion shrank significantly.